IMPLEMENTASI ALGORITMA RC6 DALAM PENGAMANAN FILE PADA BP2RD SU SAMSAT SEI RAMPAH - mhd heri sofyan (STMIK KAPUTAMA, 2022)
Confidentiality and data security are very important things in communication, both for the purpose of shared security and for individual privacy, so the current development of science and technology has affected all aspects of human life. At the North Sumatra Regional Revenue and Retribution Management Agency (BP2RD SU) SAMSAT Sei Rampah there is still very little security for a file because each data is not only stored on one computer and if needed, the file will be copied to anyone who asks for the file. That way the file is no longer guaranteed security and confidentiality. Anyone can easily retrieve files by copying and one way is data encryption or encryption. Meanwhile, RC6 can break 128-bit blocks into 4 32-bit blocks and this algorithm can work with 4 32-bit registers A, B, C, and D, then analysis on RC5 shows that the number of rotations that occur in RC5 is not entirely dependent on the data contained in the block. In addition, differential cryptanalysis attacks also proved to be able to penetrate the security offered by RC6.